2010
DOI: 10.1111/j.1439-0434.2010.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of the Population of Alternaria solani in Brazil

Abstract: Understanding the genetic structure of the population of Alternaria solani (AS) is an important component of epidemiological studies of early blight, a severe disease that affects potato (Po) and tomato (To) worldwide. Up to 150 isolates obtained from both hosts were analysed with RAPD and AFLP markers to estimate the amount and distribution of genetic variability of AS in Brazil. Using RAPD, gene diversity (h = 0.20) and scaled indices of diversity of Shannon (H¢ = 0.66) and Stoddart and TaylorÕs (G = 0.31) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Isolates obtained from contiguous tomato and potato fields such as in Margahayu, Lembang, could possibly originate from a tomato field infected with an adapted lineage to this host. Other studies in the USA, Brazil and Cuba found population subdivision according to the host of origin as detected by RAPD and/or AFLP markers (Weir et al 1998;Martinez et al 2004;Lourenço et al 2011) as well as by sequence analyses of ITS region of rDNA and the genes encoding glyceraldehyde-3-phosphate dehydrogenase (gpd), and Alt a1 (Lourenço et al 2009). …”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 96%
See 4 more Smart Citations
“…Isolates obtained from contiguous tomato and potato fields such as in Margahayu, Lembang, could possibly originate from a tomato field infected with an adapted lineage to this host. Other studies in the USA, Brazil and Cuba found population subdivision according to the host of origin as detected by RAPD and/or AFLP markers (Weir et al 1998;Martinez et al 2004;Lourenço et al 2011) as well as by sequence analyses of ITS region of rDNA and the genes encoding glyceraldehyde-3-phosphate dehydrogenase (gpd), and Alt a1 (Lourenço et al 2009). …”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 96%
“…Studies in USA, Cuba, Brazil, India and China using isozyme and molecular markers also found no location effect or no clear differentiation of A. solani collected from various regions in those countries (Petrunak and Christ 1992;Weir et al 1998;Martinez et al 2004;Varma et al 2006;Kumar et al 2008;Lourenço et al 2011;Leiminger et al 2013;Meng et al 2015). Isolates from different agroclimatic conditions were found to be more genetically similar than isolates in close proximity to one another (Kumar et al 2008).…”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 96%
See 3 more Smart Citations